Sinocrassula ganluoensis (Crassulaceae), a new species from China - Li, Rong-Juan; Zhao, Jing; Fang, Shao-Li; Chen, Chao; Luo, Miao; Zhou, Xin-Mao; Wang, Jia-Guan (Phytotaxa, 2024)
Sinocrassula Berger is a member of the Crassulaceae. Here, we have described and illustrated Sinocrassula ganluoensis, a new species distributed in Sichuan Province, based on both morphology and molecular evidence. The new species can be easily distinguished from other Sinocrassula species. Morphologically, S. ganluoensis is similar to S. ambigua, S. indica var. obtusifolia, and S. jiaozishanensis in having glabrous plant and reddish-purple petals, but the new species has plants compact rosettes, orbicular-lanceolate basal leaves, and nearly quadrate nectar scales. Phylogenetic analysis also showed that S. ganluoensis forms an independent branch.